Boganmeldelser - Per Henrik Lindblom; Per Lindegaard; Thorsten Cars; Lennart Geijer; Knut Papendorf; Stig L. Age; Christian Diesen; Nils Jareborg; Lars Lidberg; Margaretha Järvinen; Vagn Greve (Nordisk Tidsskrift for Kriminalvidenskab)
Intet resumé